"Get Off My Property": A Personal Narrative Addressing Violence Against African Americans by Law Enforcement Post–Hurricane Katrina. Issue 3 (6th July 2019) - Whittaker, Tyra Turner
Abstract : Thousands of African American New Orleanians were displaced in the aftermath of Hurricane Katrina. It appeared that every African American suddenly became a suspect, "fair game" to be hunted, especially by the police. This autoethnography chronicles the author's personal background, experiences, and resulting emotions of her father's encounter with law enforcement post–Hurricane Katrina. Law enforcement–initiated interventions are explored. The article concludes with recommendations for members of the counseling profession and law enforcement. Miles de personas afroamericanas de Nueva Orleans perdieron sus hogares como consecuencia del huracán Katrina. Y de repente, cada persona afroamericana pareció convertirse en sospechosa, "presa legítima" para la caza, especialmente por parte de la policía. Esta autoetnografía documenta los orígenes personales y experiencias de la autora, así como las emociones resultantes de la interacción de su padre con las fuerzas policiales tras el huracán Katrina. Se exploran las intervenciones iniciadas por las fuerzas policiales. El artículo concluye con una serie de recomendaciones para los profesionales de la consejería y las fuerzas policiales.